2022
DOI: 10.3389/fnut.2021.786742
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Index Predicts Survival in Patients With Breast Cancer Treated With Neoadjuvant Chemotherapy

Abstract: Nutritional risk index (NRI) is an index based on ideal body weight that aims to present body weight and serum albumin levels. It has been utilized to discriminate patients at risk of postoperative complications and predict the postoperative outcome of major surgeries. However, this index remains limited for breast cancer patients treated with neoadjuvant chemotherapy (NACT). The research explores the clinical and prognostic significance of NRI in breast cancer patients. This study included 785 breast cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Poor nutritional status not only accelerates the progression of cancer, but also deeply impacts the tolerability and acceptability of anticancer treatments, creating a vicious cycle that involves overall QoL [ 13 , 23 ] and reduces the effectiveness of chemotherapy protocols and the final prognosis [ 13 , 24 , 25 ]. Nonetheless, malnutrition and cachexia in cancer patients are still undetected and underestimated in medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Poor nutritional status not only accelerates the progression of cancer, but also deeply impacts the tolerability and acceptability of anticancer treatments, creating a vicious cycle that involves overall QoL [ 13 , 23 ] and reduces the effectiveness of chemotherapy protocols and the final prognosis [ 13 , 24 , 25 ]. Nonetheless, malnutrition and cachexia in cancer patients are still undetected and underestimated in medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer patients, undetected or unaddressed malnutrition leads to severe adverse outcomes and an unfavorable prognosis [ 7 ]. Malnourished breast cancer patients tolerate fewer cycles of chemotherapy and radiotherapy and are susceptible to treatment toxicities, treatment failures, and rapid progression of the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malnourished breast cancer patients also face repeated hospitalizations and higher treatment costs. Malnutrition also increases mortality among cancer patients by 2 to 5 times than non-malnourished cancer patients [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional risk index (NRI) incorporates changes in patient weight and serum albumin levels, making it an accurate scoring system for evaluating the nutritional status of cancer patients (14). Numerous studies have revealed a significant association between NRI and clinical outcomes in a variety of cancer types, including gastric cancer (15)(16)(17). Patients with gastric cancer with pyloric stricture who received preoperative parenteral nutrition have a unique nutritional status and the predictive ability of the NRI for them has remained to be clarified.…”
Section: Introductionmentioning
confidence: 99%